FollowTheSutures: Piloting a new way to administer onabotulinumtoxinA for chronic migraine. (June 2022) - Stovner, Lars Jacob; Hagen, Knut; Tronvik, Erling; Bruvik Gravdahl, Gøril; Burstein, Rami; Dodick, David W
Background: Anatomical and experimental data indicate that onabotulinimtoxin A could be more efficient and cost-effective for treating chronic migraine with injections targeting the cranial sutures, where collaterals from the meninges penetrate the skull. Methods: A new injection paradigm (FollowTheSutures) was tested for safety, tolerability and feasibility in a Phase II, open-label, non-controlled, single-center pilot study. Ninety units of onabotulinimtoxin A (Botox®), were injected in 18 sites over the area of the cranial sutures. Adverse events and potential beneficial effects were recorded in a headache diary at least 4 weeks before, and for 12 weeks after the injections. A higher dilution than normal of onabotulinimtoxin A was used to get better diffusion. Results: Nineteen (of 20 included) women with chronic migraine received the injections and were evaluable. There was only one treatment-related adverse event (reduced power of chewing for some weeks). Otherwise, the procedure was overall well tolerated. Patients improved on most efficacy parameters after the injections. There was little or no effect on glabellar or forehead lines. Conclusions: The protocol was safe and well tolerated. Lower risk of unblinding due to the absence of cosmetic effects should make the injection procedure well suited for a large, randomized, placebo-controlled study. If efficacy is confirmed, it will be markedly less costly than the standard procedure. Trial registration: EUDRACT (2017-002516-13), ClinicalTrials.gov (NCT03543254).